Whole blood DNA methylation aging markers predict colorectal cancer survival: a prospective cohort study - Gao, Xin; Zhang, Yan; Boakye, Daniel; Li, Xiangwei; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Clinical epigenetics, 2020)
Blood DNA methylation-based aging algorithms predict mortality in the general population. We investigated the prognostic value of five established DNA methylation aging algorithms for patients with colorectal cancer (CRC).